Recent Publications (Quarterly Journal of Economics, 1955)
Recent Publications Get access The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 648–650, https://doi.org/10.1093/qje/69.4.648 Published: 01 November 1955